Mixed Ligand Complexes of Alkali Metal Salts of Some Organic Acids with Isonitroso Ethylacetoacetate - Singh, R.N.; Gupta, G.S.P.; Kumar, B.; Singh, A.K. (Asian Journal of Chemistry, 2010)
Some mixed ligand complexes of alkali metal salts of 1-nitroso- 2-naphthol. 8-hydroxy quinoline, o-amino phenol, o-amino benzoic acid, o-nitro benzoic acid with isonitroso ethylacetoacetate have been synthesised and characterised on the basis of elemental analysis, conductivity measurement and IR spectral data.